Digital Teaching and Learning in Higher Education Developing and Disseminating Skills for Blended Learning - Chechurin, Leonid (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the challenges and opportunities faced by universities as they move to digital education. The COVID-19 pandemic as well as students' increasing levels of comfort with digital technology has accelerated the digitalization of learning and teaching, even among teachers who are less confident. The editor and contributors ask how successful digital teaching materials can be developed, what are the unique benefits of this type of teaching and how it can be linked with industry and society so as to better aid the development of student learning. The book maintains that the digital educator should be able to orchestrate diversity in the supply of digital teaching materials and project-based learning to meet the needs of students and prepare them for their future careers. Leonid Chechurin is Professor for Industrial Engineering and Management Unit of School of Engineering Science or Lappeenranta-Lahti University of Technology, FINLAND.
Chapter 1. Lecturer as Program Manager: Lessons Learned from Designing and Online Teaching a Project-Based Master Course to Engineers -- Chapter 2. Remote labs for engineering students: studying photovoltaics as energy source -- Chapter 3. Modern University Teaching Strategies -- Chapter 4. Key Learning Frameworks Required for Effective eCourse Syllabus Design -- Chapter 5. Interdisciplinary training in the virtual environment for professional activities: the experience of Gubkin University -- Chapter 6. A Framework for Effective eCourse Syllabus Design -- Chapter 7. University students' perception of blended and flipped learning (case of Tomsk universities) -- Chapter 8. Designing a framework to develop a flipped CEPHEI course in innovation systems and technological development -- Chapter 9. Creating Better Educational Videos -- Chapter 10. Technology for Creating Videos -- Chapter 11. Neuroscience-Based Learning -- Chapter 12. Problem-based flipped learning in higher education -- Chapter 13. Increasing pedagogical knowledge in higher education by explainable student agency analytics -- Chapter 14. University Students' Perceptions of Scripted Computer-Supported Collaborative Writing: Enabling and Hindering Factors -- Chapter 15. Transformation of University teaching methods: crisis and new sustainable forms of education process -- Chapter 16. Flipped Classroom: case study over 5 years -- Chapter 17. Learning Analytics Overview: Academic Approach and Machine Learning Possibilities -- Chapter 18. Digital education enables cooperation with industry -- Chapter 19. Challenges and prospects of the online education due to the COVID-19 pandemic -- Chapter 20. The Model and Realization of Electronic Education for Enterprise Innovation Engineers.
Keywords: Educational technology; Education, Higher; Teaching; Digital Education and Educational Technology; Higher Education; Pedagogy